Natural contents of heavy metals in soils of the southern Amazonas state, Brazil - Da Silva Costa, Rubia Darivanda; Neto, Pérsio Paula; Campos, Milton César Costa; Do Nascimento, Willian Barros; Do Nascimento, Clístenes Williams Araújo; Silva, Laércio Santos [UNESP]; Da Cunha, José Mauricio (Universidade Estadual de Londrina, 2017)
Heavy metals occur naturally in the soil as a product of rock weathering and, are commonly associated with environmental pollution and toxicity to living beings. This association deserves much attention since some heavy metals, such as Fe, Mn, Cu, Zn, and Ni, are essential to plants. Our attention should thus be drawn not only to the element itself, but also to its contents in the soil. This is because its occurrence and quantities are covariates of the geomorphic, geologic, pedologic, and anthropogenic diversity. In this context, the present study aimed to determine the natural contents of heavy metals in the soils of three physiographic regions of the south of Amazonas state, comparing them to natural contents in some other Brazilian soils. Twenty-four soil samples were collected in three physiographic regions (field/forest, animated relief, and flooded/non-flooded areas), in the superficial and subsurface horizons. The digestion of the samples was based on the EPA-3051A method and the determination by atomic absorption spectrophotometry (AAnalyst 800 Perkin Elmer). The results indicate a low potential of soils from the south of Amazonas in supplying heavy metals, which were found in the following decreasing order: Ba>Fe>Cr>Pb>Zn>Cu>Mn>Co>Cd. The natural heavy metal contents vary depending on the type of soil, weathering level, and physiographic regions, and are similar or inferior to those observed in other regions of the country; with Neosols presenting the highest natural contents; and Cambisols, the lowest, for most of the metals evaluated.
Keywords: Amazonas; Micronutrients; Natural metal concentration